Penerapan Model Pembelajaran Kooperatif Teknik Kancing Gemerincing dalam Upaya Meningkatkan Hasil Belajar Siswa - Largo Fitson; Syaiful M; Yustina Sri Ekwandari (FKIP UNIVERSITAS LAMPUNG, 2018)
The purpose of this study is to improve student learning outcomes through the application of Cooperative Learning Model of kancing gemerincing technique. The type of research used is Classroom Action Research (PTK) which consists of two cycles, where each cycle consists of planning, implementation, observation and reflection. The results showed that the students' learning outcomes before the implementation of Cooperative Learning Model kancing gemerincing technique 41.67% of students who completed and are in the category of